Justification of antiadhesive components choice for the composition of effervescent tablets with thick extract of betula verrucosa leaves - O. O. Chumak; Ye. A. Bezrukavyi (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Abstract